Procyclical asset management and bond risk premia - Alexandru Barbu; Christoph Fricke; Emanuel Mönch (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
We use unique institutional securities holdings data to examine the trading behaviour of delegated institutional capital and its impact on bond risk premia. We show that institutional fund managers trade strongly procyclically: they actively move into higher yielding, longer duration and lower rated securities as yields fall and spreads compress, and vice versa. Funds more exposed to negative yields increase their risk-taking more strongly, and this effect is particularly pronounced for those offering explicit minimum return guarantees. Institutional funds' investments have large and persistent price impact in both corporate and sovereign bond markets. We provide evidence that this procyclical behaviour is driven by career concerns among institutional fund managers.
Keywords: G11; G23; E43; 330; Institutional funds; institutional accounts; procyclical asset management; portfolio rebalancing; price impact; demand pressures; asset price volatility; career concerns